L’Autore si dilegua: “morte dell’autore” e “libri latenti” - Russo, Fabiana (Status Quaestionis, 2023)
The essay proposes, at first, a historical-critical reconstruction of the debate on authorship developed in the second half of the Twentieth century. The second part aims to apply Roland Barthes’s concept of “death of the author” to the publishing category of “libri latent”, as Domenico Scarpa defines them, proposing a different philological approach to this category.